SPEECH ACT PRESENTATION IN A LOCALLY-WRITTEN ENGLISH TEXTBOOK - Nurdiana Nurdiana Nurdiana (Journal of English Language and Culture, 2022)
A textbook is developed to provide language input for language learners. The input should contain appropriate language use to assist learners to be able to communicate effectively from the communicative competence perspective which focuses on pragmatics. For this reason, the present study attempts to investigate speech act presentation in a local English textbook from  metapragmatic, sociopragmatic, and pragmalinguistics  point of view.  The data were taken from common phrases or language expressions of particular functions integrated with conversations in the textbook. Findings revealed that the the speech acts investigated in the textbook were presented in more discrete items lacking sociopragmatic and pragmalinguistic information. Concerning metapragmatic information, there seems to be a significant correlation between metapragmatic, sociopragmatic, and pragmalinguistic aspects. Pedagogically, it implies that the speech acts exposed through the textbook may not serve communicative functions as it was supposed to be and therefore, the textbook did not contain adequate pragmatic knowledge which may cause fewer opportunities to reach communicative competence.